Characteristics of complete tibial fractures in California racehorses. (27th November 2020) - Samol, Monika A.; Uzal, Francisco A.; Hill, Ashley E.; Arthur, Rick M.; Stover, Susan M.
Abstract: Background: Tibial fractures cause ~3% of racehorse deaths. Pre‐existing stress fractures have been associated with multiple racing and training fractures, but not complete tibial fractures. Objectives: To describe racehorse tibial fractures and compare signalment and exercise histories of affected and control racehorses. Study design: Retrospective analysis of necropsy reports. Methods: Racehorses that had a complete tibial fracture (1990‐2018) were retrospectively reviewed. Signalment and exercise histories of affected horses were compared to 1) racehorses that died because of non‐tibial musculoskeletal injuries or 2) non‐musculoskeletal cause and 3) age, sex, event‐matched control racehorses. Tibial fracture prevalence was described relative to California racehorses that had at least one official work or race. Age, sex and limb distributions were compared between affected and control horses (Chi‐square, Fisher's Exact test). Exercise history data were reduced to counts and rates of official high speed works, races and layups (periods without an official high speed work or race >60 days). Variables were compared among groups using matched logistic regression ( P  ≤ .05). Results: Tibial fractures in 115 horses (97% unilateral; 50% left, 47% right) occurred most commonly during training (68%) and in 2‐ to 3‐year‐old horses (73%). Fractures were predominantly comminuted (93%), diaphyseal (44%) and oblique (40%). Of 61 cases examined for callus, 64% had periosteal callus associated with fracture, most commonly in proximal (65%) and distal diaphyseal (27%) locations. Of 28 racehorses with known exercise history, 57% never raced and 36% had a layup. Affected horses had fewer official‐timed works and events (official high speed works and races), number of active days and accumulated less distance in events and works ( P  < .05) than control horses. Main limitations: Retrospective review of necropsy reports by multiple pathologists over 28 years. Conclusions: Tibial fractures were associated with pre‐existing stress fracture early in career. Most fractures were associated with proximolateral stress fractures.